Mixed provenance of organic carbon in Northeast Atlantic temperate intertidal seagrass sediments - Emma A. Ward; Sarah E. Reynolds; Melanie J. Leng; Jack H. Lacey; Marianna Cerasuolo; Bronwen Paxton; Federica Ragazzola; Joanne Preston (Scientific Reports)
Abstract Blue carbon accreditation for climate mitigation services provided by coastal ecosystems, such as seagrass beds, typically account only for autochthonous organic carbon, potentially underestimating the total carbon sequestration capacity of seagrass ecosystems. Here, a multi-proxy approach is used to determine the provenance of organic carbon in two intertidal temperate seagrass ecosystems in the Northeast Atlantic. The organic carbon to nitrogen ratio (Corg/N) and carbon isotope composition (δ13C) of seagrass tissues and sediments from an open coastal sandy site (Ryde, UK) and a muddy tidal inlet site (Farlington Marshes, UK) were measured. Sedimentary Corg/N was higher at the muddy site than the sandy site, suggesting a greater contribution of marine algal organic matter in the latter. Isotopic mixing model analysis showed that seagrass biomass contributes between 12 and 25% to accumulated sedimentary Corg. These findings demonstrate that temperate Northeast Atlantic seagrass sediments are dominated by allochthonous Corg (75–88%) and that current blue carbon accreditation frameworks undervalue these ecosystems. Supporting the estimation and uptake of high integrity field-derived allochthonous deduction evidence would assist uptake of these frameworks to support implementation of nature-based solutions.